Diagnostic Accuracy of Endoscopic Findings (Duodenal Fissuring) in Diagnosis of Celiac Disease - Wajid Iqbal, Noman Khan, Samid Ullah, Muhammad Ibrahim Saeed, Faisal Wasim Ismail, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aims to determine the diagnostic accuracy of endoscopic findings, specifically duodenal fissuring, in the diagnosis of celiac disease, thus contributing to a more efficient and accurate diagnostic approach in clinical practice. Study Design: A descriptive cross-sectional study was employed to assess the diagnostic accuracy of endoscopic findings in the diagnosis of celiac disease. Setting: The study was conducted at the Endoscopy Suite, Section of Gastroenterology, Department of Medicine, Aga Khan University Hospital, Karachi. Duration: The research was carried out over six months, from 30-06-20 to 30-12-20, following the approval of the synopsis. Methods: A sample of 130 patients presenting with clinical suspicion of celiac disease was recruited for this study. Participants underwent upper gastrointestinal endoscopy, with duodenal biopsies obtained for histopathological analysis. The presence of duodenal fissuring was recorded, and the diagnostic accuracy of endoscopic findings was evaluated against histopathological results as the gold standard. Results: Our findings demonstrate a strong correlation between the presence of duodenal fissuring and the diagnosis of celiac disease. The endoscopic findings revealed a sensitivity of 80.0%, specificity of 92.3%, positive predictive value of 88.9%, negative predictive value of 85.3%, and an overall diagnostic accuracy of 85.4% for celiac disease. Conclusion: The study concludes that endoscopic findings, particularly duodenal fissuring, offer a high diagnostic accuracy in the identification of celiac disease. Incorporating these findings into the diagnostic algorithm can significantly enhance clinical decision-making and contribute to a more efficient and accurate diagnosis of celiac disease. Keywords: celiac disease, diagnostic accuracy, endoscopic findings, duodenal fissuring, upper gastrointestinal endoscopy, histopathology, sensitivity, specificity